A Study On Effectiveness Of Child-Centered And Play-Based Home Support Education Program On Children Who Have Development Problems - (:unkn) unknown (HACETTEPE UNIV, 2017)
This study was conducted with four participants at high risk for autism, who consulted a psychiatrist independent of the study, due to their families noticing developmental abnormalities. This study presents four months, six months, two years - three months and one year - ten months durations based results of the four participants of the play-based home support educational program respectively. Semi-experimental research methods with a single group pretest-posttest model were used in this study. It was observed that the application of a play-based home support and child-centered educational programs to four children of different ages demonstrated strong symptoms of autism resulted in improvements in all sub-scales of ADSI(AGTE), with greater developments specifically in the linguistic-cognitive scale. Results of the ABC, despite the fact that the educational program was administered to each child for different lengths of time; indicated an observable decline in autism symptoms in all sub-areas.
Keywords: Play-based education; home support; special education; AUTISM SPECTRUM DISORDERS; YOUNG-CHILDREN; EARLY INTERVENTION; PRESCHOOL-CHILDREN; TRAINING-PROGRAM; JOINT ATTENTION; PROJECT; PREDICTORS; BEHAVIORS; PARENTS